Sociocultural Functions of Choral Art in Subcarpathian Ruthenia in the 1920s–1930s - Тетяна Росул (Культура і мистецтво у сучасному світі, 2023)
The aim of the article is to identify the institutionalisation level of the musical culture of Subcarpathian Ruthenia during the interwar period, to reveal the sociocultural functions of choral music in the region, and to determine the index of society's involvement in choral singing. Research results indicate an increase in the institutionalisation level of the region’s musical culture in the 1920s–1930s, involving broad segments of the population in choral performance. Active amateur and professional choral activities became indicators of growing national self-awareness and self-affirmation through various forms of civic and creative activities. Choral music became an effective means of patriotic education for the youth, the basis for the development of the region’s musical education, and a polylogue of ethnic musical traditions. The scientific novelty lies in defining the basic sociocultural functions of the choral art of Subcarpathian Ruthenia during the interwar period. The criteria for systematisation are the social and aesthetic needs of the region’s residents, the features of their national self-awareness, creative, and economic resources. Choral art is considered as an element of the general cultural process determined by social and historical events. Conclusions. The cultural life of Subcarpathian Ruthenia in the 1920s–1930s proves the multifunctionality of choral art. However, the sociocultural functions of choral music varied in intensity. The choir became a kind of sociocultural environment that served as a factor in attracting the population to spiritual and aesthetic values, fostering the creative realisation of individual moral potential, and representing the entire set of cultural activities of ethnic groups. Choral art emerged as a powerful ethno-creative force that used various forms of representing ethnic identity, demonstrating social aspirations, and preserving traditions.